2022
DOI: 10.3390/app122211354
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Road Crash Severity Using Classifier Models and Crash Hotspots

Abstract: The rapid increase in traffic volume on urban roads, over time, has altered the global traffic scenario. Additionally, it has increased the number of road crashes, some of which are severe and fatal in nature. The identification of hazardous roadway sections using the spatial pattern analysis of crashes and recognition of the primary and contributing factors may assist in reducing the severity of road traffic crashes (R.T.C.s). For crash severity prediction, along with spatial patterns, various machine learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Tere is no reference value of Moran's I that indicate autocorrelation, but a signifcant p value indicates the relevance of autocorrelation. Several previous studies reported a moderately high Moran's I of 0.32 [30] or 0.30 [31] at the signifcance level of 1%, but some studies reported a low Moran's I in the range of 0.1-0.2 [32] or less than 0.1 [33,34]. Global spatial autocorrelation is useful when identifying the overall spatial correlation of certain areas presented within the research scope, but there are also limitations.…”
Section: Spatial Autocorrelationmentioning
confidence: 98%
“…Tere is no reference value of Moran's I that indicate autocorrelation, but a signifcant p value indicates the relevance of autocorrelation. Several previous studies reported a moderately high Moran's I of 0.32 [30] or 0.30 [31] at the signifcance level of 1%, but some studies reported a low Moran's I in the range of 0.1-0.2 [32] or less than 0.1 [33,34]. Global spatial autocorrelation is useful when identifying the overall spatial correlation of certain areas presented within the research scope, but there are also limitations.…”
Section: Spatial Autocorrelationmentioning
confidence: 98%
“…In addition, in Ref. [14], the KPSIT C50 dummy was compared with a simulation dummy made in the MSC ADAMS program. Ref.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The driver's position has changed, and current vehicles allow you to adjust the height of the steering column and adjust the vehicle seat to suit the comfort of the driver and passengers. The road infrastructure has also changed significantly [13][14][15]. In many countries around the world, highways and expressways have been expanded, forcing vehicles to move in one direction, which has resulted in a reduction in the number of frontal and side accidents in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the qualities directly related to the accidents contribute significantly to the magnitude of such accidents [ 10 ]. Among these factors are the speed at which the car was hit by the other vehicle, also known as the second automobile [ 12 ], the number of cars involved in the incident [ 13 ], and the congestion level.…”
Section: Introductionmentioning
confidence: 99%